Role of Prostaglandin E2 in the Modulation of Wnt Canonical Signaling in Cells on Microstructured Titanium Surfaces. Issue 2 (May 2016) - Manfredi, Edoardo; Lumetti, Simone; Rivara, Federico; Toffoli, Andrea; Calciolari, Elena; Cacchioli, Antonio; Ravanetti, Francesca; Ghiacci, Giulia; Macaluso, Guido; Galli, Carlo
Background: Rough surface topography enhances the activation of Wnt canonical signaling, a pathway required for osteoblast differentiation. The present study investigated the effects of the modulation of prostaglandin E2 (PGE2 ) signaling on osteoblastic differentiation on titanium surfaces for endosseous implants with different topographies. Methods: C2C12 cells were plated on polished or acid-etched/sand-blasted (SLA) titanium discs and stimulated with 1 μM PGE2 or 100 nM cyclooxygenase inhibitor indomethacin. Activation of Wnt canonical signaling was measured with a reporter system. Gene expression was measured in the same cell system by real-time polymerase chain reaction (RT-PCR). Osteoblastic MC3T3 cells were then plated on polished or SLA titanium discs with or without indomethacin, and their proliferation and the expression of osteoblast-specific genes was assessed by RT-PCR. Cell morphology was furthermore studied on SEM, and cell adhesion was assessed by fluorescent labeling of focal adhesion. Results: PGE2 decreased Wnt signaling stimulation in cells growing on polished or SLA surfaces, while indomethacin increased the expression of Wnt target genes in C2C12 and MC3T3 cells, by reporter assay. Moreover, indomethacin increased the expression of early differentiation marker alkaline phosphatase in MC3T3 cells on polished discs and of late marker osteocalcin in cells on SLA titanium. Conclusions: Prostaglandin signaling affects the activation of Wnt canonical pathway in osteoblastic and mesenchymal cells on microstructured surfaces.